Chernysh Anna. Intertextual structure of M. Slaboshpytskyi novels-biographies - Chernysh Anna (Philological Treatises, 2020)
The paper analyzes the intertextual construction biographical prose M. Slaboshpitskiy’s: quotes, proverbs, sayings, fairy tale, a reference to the Greek myth and the like; noted their function and semantic role in the structure of the work.